Radical Democracy: Syriza, a Left-Populist Party's Approach to Addressing (or Entrenching?) Precarious Employment and Implications for Thai Politic - Kruanopparatana, Phuriphat (King Prajadhipok’s Institute Journal, 2025)
Syriza is a left-wing populist party from Greece. One of its main policies is addressing the "precarity of the people's lives," which has resulted from the neoliberal economic regime, by radicalizing democracy. However, this article will explore whether Syriza's explanations and proposals for solving this problem will lead to a solution or a dead end for the issue of precarity or precariousness. It finds that there have been several studies on precarity in Greece, and these studies define precarity differently, focusing on social precarity and precarious employment. Finally, the article will discuss whether the integration of small-scale employers and employees under the concept of "the people" will act as an empowering force or become an obstacle to overcoming the precarious employment system. At the same time, progressive parties in Thailand that strive to solve political and economic problems face challenges related to precarity and precarious employment, as noted in this paper, which they need to overcome.